2019
DOI: 10.1016/j.euf.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Versus Hypofractionated Radiation Therapy for Localized Prostate Cancer: A Meta-analysis of Randomized Noninferiority Trials

Abstract: Treatment with a shorter course of radiation, using higher doses per treatment over fewer days, may be the preferred approach in appropriately selected patients with localized prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
1
25
0
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12] These trials have demonstrated that moderate hypofractionation (eg, 20 treatments) has comparable efficacy and toxicity data to the conventional 37 treatments of radiation therapy. [5][6][7][8][9][10][11][12] Stereotactic body radiation therapy (SBRT) represents an extreme form of hypofractionation in which treatment is usually delivered in 4-7 fractions. Development and optimization of this ultrahypofractionation technique over the last 20 years has resulted in incorporation of SBRT into routine clinical practice, and SBRT is now a standardof-care treatment option for many tumors of the lung, brain, spine, liver, and pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] These trials have demonstrated that moderate hypofractionation (eg, 20 treatments) has comparable efficacy and toxicity data to the conventional 37 treatments of radiation therapy. [5][6][7][8][9][10][11][12] Stereotactic body radiation therapy (SBRT) represents an extreme form of hypofractionation in which treatment is usually delivered in 4-7 fractions. Development and optimization of this ultrahypofractionation technique over the last 20 years has resulted in incorporation of SBRT into routine clinical practice, and SBRT is now a standardof-care treatment option for many tumors of the lung, brain, spine, liver, and pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] A meta-analysis pooling data from three of these RCTs (each of non-inferiority design) demonstrated that H-RT was associated with a significantly increased risk of clinicianassessed acute (3 month) gastro-intestinal (GI) toxicity (predominantly grade 2 using Radiation Therapy Oncology Group criteria), which did not translate into late toxicity (median follow-up 5.2 -6 years). 8 However, H-RT was reported to be associated with an increase in late Grade ≥2 genitourinary (GU) toxicity. 8 It is generally accepted that patient-reported outcomes (PROs) detect more reliably adverse treatment effects relevant to patients than clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, H-RT was reported to be associated with an increase in late Grade ≥2 genitourinary (GU) toxicity. 8 It is generally accepted that patient-reported outcomes (PROs) detect more reliably adverse treatment effects relevant to patients than clinical data. [9][10][11] However, there is limited evidence on how PROs in urinary, bowel and sexual function vary by RT regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Another particular reason is that a demonstrated need of pelvic RT would put into questions the use of moderately hypofractionated RT scheme (20 sessions) that have been shown to be at least equivalent in terms of progression free survival (PFS) with no or few increase of late toxicity compared to conventionally fractionate scheme (13,14). Indeed, most of these RT scheme used in daily practice are based on 20 fractions, whereas schemes with pelvic RT are based on conventional fractionation with at least 23 to 25 sessions for lymph nodes irradiation and 35 to 40 sessions to the prostate.…”
Section: Editorial Commentarymentioning
confidence: 99%